Combined Amperometry and Electrochemical Cytometry Reveal Differential Effects of Cocaine and Methylphenidate on Exocytosis and the Fraction of Chemical Release. Issue 13 (18th February 2019) - Zhu, Wanying; Gu, Chaoyi; Dunevall, Johan; Ren, Lin; Zhou, Xuemin; Ewing, Andrew G.
Abstract: Amperometry with nanotip electrodes has been applied to show cocaine and methylphenidate not only trigger declines in vesicle content and exocytotic catecholamine release in a model cell line but also differentially change the fraction of transmitter released from each individual vesicle. In addition, cocaine accelerates exocytotic release dynamics while they remain unchanged after methylphenidate treatment. The parameters from pre‐spike feet for the two drugs are also in opposition, suggesting this aspect of release is affected differentially. As cocaine and methylphenidate are psychostimulants with similar pharmacologic action but have opposite effects on cognition, these results might provide a missing link between the regulation of exocytosis and vesicles and the effect of this regulation on cognition, learning, and memory. A speculative chemical mechanism of the effect of these drugs on vesicle content and exocytosis is presented. Abstract : All around my brain : Single‐cell amperometry and intracellular vesicle impact electrochemical cytometry with nanotip electrodes were employed to investigate the effects of cocaine and methylphenidate on exocytosis and the fraction of chemical release in PC12 cells. These drugs have differential effects on exocytosis dynamics as well as the release fraction.